(untitled) (Revista Escenarios Sociojurídicos, 2022)
Currently, the phenomena of people or groups in masses that must leave their places of origin, are more visible and statistically analysable, due, among other things, to the controls exercised by the States and to the amount of literature that has been written on migration. Of course, that there is a descriptive need that allows us to show the magnitude of the problem and the deficiency of the Colombian legal system to address the Venezuelan migration phenomenon in Health, being the purpose of this article to identify from the legal point of view, the mechanisms for the guarantee of said right to this population.